Beliefs of pre-service teachers regarding future teaching practice - Perdomo-López, Carmen de los Ángeles; Pérez-Jorge, David; González-Afonso, Miriam Catalina (Frontiers in Education, 2025)
The initial teacher training and the beliefs about their role in the classroom that prospective teachers acquire throughout their training significantly impact the construction of their teaching identity and influence their professional practice. Understanding these beliefs is crucial, as they act as filters that shape how future teachers interpret teaching-related information. This study focuses on analyzing the beliefs of future secondary education teachers, specifically students enrolled in the Master’s Degree in Teacher Training at the University of La Laguna (ULL). A mixed methodology was used. Quantitative data were collected through a questionnaire on beliefs about teacher training in secondary education. This questionnaire was administered to 207 students at the beginning and end of the 2022–2023 academic year. Qualitative data were obtained from a focus group with participation from study subjects. The findings indicate that there are no significant differences in beliefs regarding disciplinary knowledge, a practical training model, and teaching vocation after completing initial training. These results suggest that certain core beliefs about teaching remain stable throughout the initial teacher training process, highlighting the need to reflect on how teacher education programs can more effectively influence the belief systems of future educators.